Case Analysis on Partial Discharge Signal of XLPE Cable T-Joint by Using High-Frequency Pulse Current Method. (December 2017) - Hao, Zhang; Yubing, Duan; Bin, Wang; Hui, Liu; Ying, Lin; Xiaoli, Hu; Rong, Liu; Miao, Wang
Abstract: The cable joint is a vital part of cable lines which cause defects and faults easily and through partial discharge (PD) test internal discharge can be noticed. In this paper, we study a suspected PD signal which was found in the T-joint and intermediate joints nearby during a 110kV XLPE cable partial discharge (PD) test. Through the high-frequency PD detection technology, the discharge signal was positioned from the inside of T-joint. A trace of discharge was found at the air gap of the metal ring and the epoxy sleeve in the front of the T-joint stress cone. It is further verified that high-frequency PD detection technique can be used to locate the position of discharge.